EDUCATING STUDENTS' POLITENESS THROUGH DIGITAL POSTER AND REELS: STUDENTS’ INSIGHTS - Telaumbanua, Silvan; Telaumbanua , Yasminar Amaerita; Laoli, Jacqueline; Gulo, Septika Novianti; Mendrofa, Sharley Grace (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Abstract:In contemporary education, promoting politeness is essential for students' interpersonal and professional growth. Digital platforms like posters and reels provide innovative means to effectively impart these values. This qualitative study aimed to educate students about politeness using digital posters and reels, evaluating their effectiveness in conveying social etiquette. Qualitative methods involved gathering students’ feedback on digital posters and reels depicting scenarios of polite behavior. Analysis revealed diverse perceptions among students regarding the impact of digital posters versus reels. While both mediums were generally well-received, reels were favored for their dynamic engagement, whereas posters were noted for their detailed information. Digital reels prove advantageous in teaching politeness by offering interactive and engaging content. However, posters remain crucial for delivering comprehensive information. Integrating both mediums strategically can optimize educational efforts to enhance politeness among students, catering to varied learning preferences and maximizing educational outcomes.